REPUTASI AUDITOR SEBAGAI PEMODERASI PENGARUH FINANCIAL DISTRESS PADA AUDITOR SWITCHING - Widyanti, A.A. Sagung Istri Agung; Badera, I Dewa Nyoman (E-Jurnal Akuntansi; Vol 16 No 3 (2016), 2016)
This study aims to determine the effect financial distress to the auditor switching to the auditor's reputation as a moderating variable. This study was performed on companies listed on the Stock Exchange from 2010-2014. Total population of 149 companies and acquired sample number of 41 companies. Sample collection method used is a method of non-probability sampling with purposive sampling techniques and data analysis techniques used were logistic regression analysis (logistic regression) and Moderating Regression Analysis (MRA). The results demonstrated that financial distress positive effect on the auditor switching. This means that the higher the financial distress experienced by the company, the higher the tendency of companies to perform switching auditors. Reputation auditor strengthen the influence of financial distress in the auditor switching. This means that companies experiencing financial distress auditor will perform the switching and selecting a reputable auditor to improve the credibility of the company.
Keywords: Auditor Switching, Financial Distress, Reputation Auditor